2022
DOI: 10.3390/membranes12111032
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Polyphenolic Antioxidants in Apple Juice and Extract Using Ultrafiltration

Abstract: The aim of the present work was to study the potential of ultrafiltration with three polyacrylonitrile membranes (1, 10, and 25 kDa) to concentrate polyphenolic antioxidants in apple juice and extract. The permeate flux, total polyphenols, polyphenolic profile, phenolic acid content, and total antioxidant capacity were determined using the FRAP and DPPH tests, the content of water-soluble proteins during ultrafiltration was established, and the concentration factors and rejections were determined. The permeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…It was originally for the detection of tyrosine [ 36 ] and was later developed to measure the TPC [ 37 ]. Some fruit juices and their products were reported to need to be centrifuged or filtered before the determination of TPC, such as yellow peach wines that were centrifuged at 8000× g for 5 min before determination [ 38 ], sea buckthorn pulp that was centrifuged at 4000× r/min for 10 min [ 27 ], apple juice extraction that was filtered through a paper filter [ 8 ], mixed juice with blue honeysuckle juice and fermented goat milk that was centrifuged at 5000× g for 10 min [ 39 ], five kinds of smoothies including fruit and vegetables that were centrifuged at 5000× g for 5 min [ 40 ], fresh or fermented noni juice extracts that were filtered through a Nylon filter (0.22 µm, 25 mm) [ 41 ]. It is necessary to study the influence of centrifugation and filtration on the determination of polyphenols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was originally for the detection of tyrosine [ 36 ] and was later developed to measure the TPC [ 37 ]. Some fruit juices and their products were reported to need to be centrifuged or filtered before the determination of TPC, such as yellow peach wines that were centrifuged at 8000× g for 5 min before determination [ 38 ], sea buckthorn pulp that was centrifuged at 4000× r/min for 10 min [ 27 ], apple juice extraction that was filtered through a paper filter [ 8 ], mixed juice with blue honeysuckle juice and fermented goat milk that was centrifuged at 5000× g for 10 min [ 39 ], five kinds of smoothies including fruit and vegetables that were centrifuged at 5000× g for 5 min [ 40 ], fresh or fermented noni juice extracts that were filtered through a Nylon filter (0.22 µm, 25 mm) [ 41 ]. It is necessary to study the influence of centrifugation and filtration on the determination of polyphenols.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of plant polyphenols is very extensive, and the accuracy of the detection method is very important. Methods for the determination of polyphenolic compounds include spectrophotometry [ 7 ], high performance liquid chromatography (HPLC) [ 8 , 9 ], high performance liquid chromatography-mass spectrometry [ 10 ], gas chromatography (GC), and gas chromatography-mass spectrometry (GC-MS) [ 11 , 12 ]. Among them, spectrophotometry is the most commonly used method for the determination of TPC, including the Folin-Ciocalteu (F-C) assay, the Prussian Blue (P-B) assay, and the Ferrous Tartrate (F-T) assay.…”
Section: Introductionmentioning
confidence: 99%
“…where A = 0.125 m 2 is the membrane surface area in the module [9]. Rejection (R, %) and concentration factor (CF) were calculated using the following formulas:…”
Section: Experimental Systemmentioning
confidence: 99%
“…The total polyphenolic content (TPP) was established by the method of Singleton and Rossi [10] with modifications described in previous our work [9].…”
Section: Polyphenolic Contentmentioning
confidence: 99%
“…Processing is performed at mild temperatures, maintaining the original characteristics of the products processed, with minimal loss of vitamins, polyphenols, proteins, and other thermolabile compounds [ 22 , 23 , 24 ]. Recent studies demonstrated the efficiency of ultrafiltration and nanofiltration for the concentration of bioactive compounds, such as anthocyanins, flavonoids, oligosaccharides, and phenolic compounds from vegetable extracts [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%